2020
DOI: 10.3390/foods9020137
|View full text |Cite
|
Sign up to set email alerts
|

Advances in Occurrence, Importance, and Mycotoxin Control Strategies: Prevention and Detoxification in Foods

Abstract: Mycotoxins are toxic substances that can infect many foods with carcinogenic, genotoxic, teratogenic, nephrotoxic, and hepatotoxic effects. Mycotoxin contamination of foodstuffs causes diseases worldwide. The major classes of mycotoxins that are of the greatest agroeconomic importance are aflatoxins, ochratoxins, fumonisins, trichothecenes, emerging Fusarium mycotoxins, enniatins, ergot alkaloids, Alternaria toxins, and patulin. Thus, in order to mitigate mycotoxin contamination of foods, many control approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
446
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 457 publications
(452 citation statements)
references
References 273 publications
(346 reference statements)
5
446
1
Order By: Relevance
“…Ozonation is a simple technology that leaves no undesirable residues [221]. It is increasingly used to prevent the development of pathogenic fungi during storage as a strategy for the balanced control of these microorganisms [222].…”
Section: Physical Methodsmentioning
confidence: 99%
“…Ozonation is a simple technology that leaves no undesirable residues [221]. It is increasingly used to prevent the development of pathogenic fungi during storage as a strategy for the balanced control of these microorganisms [222].…”
Section: Physical Methodsmentioning
confidence: 99%
“…where: w(t) is the sigmoidal-growth function, a = w(∞), i.e., the value of w where t approaches infinity, while b is accounted for the for the slope of the curve, and c is a parameter which describes the point of inflection of the curve. Several sigmoidal models proposed by Romano [27] and Romano et al [28] derive from the mathematical model which was originally developed for describing the bacterial growth in pH-controlled batch cultures [29]. These models presented a comparison of sigmoidal models and also demonstrated that the Gompertz model was the best compromise between quality of fit and model complexity.…”
Section: Mathematical Modelling and Statistical Analysismentioning
confidence: 99%
“…Certainly, the results obtained in this study confirm the previous findings by other authors (summarized by Schaarschmidt and Fauhl-Hasse [14]) that the changes in mycotoxin concentrations during fermentation processes is largely dependent on several factors: type of mycotoxin, initial concentration of mycotoxins, pH of the dough, the dough composition, the fermentation temperature and duration, as well as the present microbial species and strains. Furthermore, recently published review by Agriopoulou et al [29] summarized data from representative studies on the occurrence, importance, and mycotoxin control strategies regarding there prevention and detoxification in foods including the possible mechanisms of action of some yeast and LAB strains on some of the mycotoxins during fermentation process. Generally, according to published studies, certain bacteria and yeast have the ability to bind mycotoxins in foods or liquids providing reduction of the mycotoxins content in the final products.…”
Section: Reduction Of Alternaria Toxins During Fermentation Of Wholementioning
confidence: 99%
See 1 more Smart Citation
“…Pre-harvest methods include good agricultural practices (GAPs) and good manufacturing practices. Crop rotation, tillage and fungicide treatment are mainly implemented to control fungal infection [19,20]. Fungicides are commonly used during agricultural practices but have numerous disadvantages such as detrimental effects on human and animal health, environmental contamination and subsequently, they have a strong impact on microbial biodiversity [21,22].…”
Section: Introductionmentioning
confidence: 99%